Symptomatic SARS-CoV2 infections in patients treated in France by hemodialysis in an establishment, or at home or by peritoneal dialysis: Data from the REIN and RDPLF registries - Cécile Couchoud; Christian Verger (RDPLF, 2020)
In France all patients treated with dialysis are registered in the REIN registry  (Epidemiology and Information Network in Nephrology) ; in addition  the RDPLF (French Language Peritoneal Dialysis Registry) monitors patients treated at home in French-speaking regions and countries. Asymptomatic patients with a positive SARS-CoV2 test were excluded :  the study focused only on patients with symptomatic COVID-19 disease. Data from REIN and RDPLF were used. In total, 3,541 patients were declared symptomatic with COVID-19. The proportion of patients with symptomatic SAR-coV2 infection was 4.9% in patients treated at home by peritoneal dialysis or hemodialysis and 8.0% in those treated in a dialysis unit. After adjustment for age and comorbidities, being treated at home was associated with a higher risk of mortality. In conclusion, home treatments could represent a solution for preventing the risk of contamination during the circulation of the virus. On the other hand, the risk of mortality in symptomatic patients at home could be linked to a delay in treatment: rigorous remote organization must be implemented so as not to delay the treatment of patients in the event of infection.